1998
DOI: 10.1111/j.1463-6395.1998.tb01159.x
|View full text |Cite
|
Sign up to set email alerts
|

The Oxygen Receptor of the Teleost Gill?

Abstract: Sundin. L. Holmgren, S. & Nilsson. S. 1998. The oxygen receptor of the teleost gill?-Acra Zoologicu (Stockholm) 7 9 207-214.The gills of the Atlantic cod, Gadus morhua. were studied using immunohistochemical techniques. Primary antibodies directed against serotonin (5-hydroxytryptamine, 5-HT) and acetylated a-tubulin were used to visualise cells containing serotonin and nerve fibres, respectively. Three morphologically different 5-HT immunoreactive cell types were distinguished: (I) Neuroepithelial cells (NECs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…those nerve fibres whose parent cell bodies are located within the gill filaments, and indicated the presence of three populations of intrinsic neurons. These observations confirmed previous reports of intrinsic neurons in teleosts Sundin et al, 1998a). The intrinsic innervation in the zebrafish gill is summarized in Fig.…”
Section: Innervation Of the Gill Filaments And Secondary Lamellaesupporting
confidence: 81%
See 1 more Smart Citation
“…those nerve fibres whose parent cell bodies are located within the gill filaments, and indicated the presence of three populations of intrinsic neurons. These observations confirmed previous reports of intrinsic neurons in teleosts Sundin et al, 1998a). The intrinsic innervation in the zebrafish gill is summarized in Fig.…”
Section: Innervation Of the Gill Filaments And Secondary Lamellaesupporting
confidence: 81%
“…2B,C). Previous studies have described nerve fibres of the gill filaments, including those identified as adrenergic, cholinergic, nitrergic and peptidergic (Donald, 1984;Donald, 1987;Dunel-Erb et al, 1982;Dunel-Erb et al, 1989;Bailly et al, 1989;Bailly et al, 1992;Sundin et al, 1998a;Zaccone et al, 2006). Only recently was innervation of the secondary lamellae characterized in zebrafish with zn-12 (Jonz and Nurse, 2003), and similar nerve fibres of the lamellae were identified in goldfish and catfish (Saltys et al, 2006;Zaccone et al, 2006).…”
Section: Innervation Of the Gill Filaments And Secondary Lamellaementioning
confidence: 98%
“…In fact, among the neuroendocrine cell elements, those positive to 5-HT prevail in the Ganzirri specimens, while in the Lesina specimens those positive to nNOS are predominant. They represent two rather distinct types of neuroepithelial cells that presumably have different anatomical distribution patterns (Burleson & Smatresk, 1990a, b;Burleson et al, 1992;Sundin et al, 1998). This also seems to be consistent with the data for the calcium-binding proteins, S-100 and Cb D28K (Fasulo et al, 1998), and the cytokeratin CK18 , which are considered markers of neuroendocrine cells.…”
Section: Discussionsupporting
confidence: 77%
“…However, the sensors for the ventilatory response to hypoxia appear to be more diffuse and variable, sensing both external and internal gas levels (Daxboeck and Holeton, 1978). For example, in the catfish, the ventilatory response to hypoxia arises only from receptors confined to the gill arches (Burleson and Smatresk, 1990), but in many fish, total gill denervation fails to eliminate the hypoxic ventilatory response (Saunders and Sutterlin, 1971;Sundin et al, 1998) and the remaining receptors appear to occur at extrabranchial sites including the orobranchial cavity (Milsom et al, 2002).…”
Section: The Location Of Ammonia Sensors In Trout Gillsmentioning
confidence: 99%
“…Because the depolarizations induced by both hypoxia and hypercapnia are blocked by the presence of quinidine, a non-specific blocker of background K + channels, but not by several blockers of voltage-dependent K + channels, it has been proposed that these stimuli cause membrane depolarization by inhibiting background K + channels (Jonz et al, 2004;Qin et al, 2010). In turn, the elevation of [Ca 2+ ] i in NECs would lead to the subsequent release of neurotransmitter for the ventilatory modulation, with 5-HT being the prime candidate (Fritsche et al, 1992;Burleson and Milsom, 1995;Sundin et al, 1998;Jonz and Nurse, 2003;Coolidge et al, 2008). Catecholamines, ACh and ATP (co-stored with monoamines in vesicles) may also play important roles as likely neurotransmitters in NEC physiology (Burleson and Milsom, 1995;Coolidge et al, 2008;Nurse, 2010).…”
Section: Necs Are Probably Ammonia Chemoreceptorsmentioning
confidence: 99%